Socialization of Increasing Creativity In The Use of Digital Technology In Improving MSMES In Rural Areas: Pengabdian - Masrifah, Ifah; Heriyana, Heriyana; Erlina, Neti; Alamsyah, Rully; Andrian, Risa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The outreach activities conducted by the author in this article were conducted in several specific villages, including Cipatik Village, West Bandung, and Danau Cala Village, Musi Banyuasin. The outreach activities were conducted over fifteen days. Hopefully with this socialization, the author's goals can be achieved in stages perfectly, starting from MSME stakeholders being able to think openly by accepting technological advances and of course their creativity will also increase, then MSME stakeholders can use digital technology well, then in the end MSME sales will increase, their income will also increase, and rural MSMEs can continue to be ongoing and even continue to develop over time.